The Roy’s adaptation model in a patient with Guillain-Barre Syndrome (GBS): a case report - Fithriyyah, Yayu Nidaul; Haryani (BKM Public Health and Community Medicine, 2021)
Purpose: The incidence of Guillain-barré syndrome (GBS) may increase during an infectious disease outbreak or pandemic. Disease progression often has an impact on the patient and family. Presents how Roy Adaptation Model (RAM) can guide nurses to assist and identify patient needs with GBS in a hospital setting. Methods: A case report. The RAM assessment uses Russo (2019) through interviews and observation, and the RAM intervention was guided by Akram Mansouri et al. (2019). Results: Patients showed adaptive behavior following RAM intervention in 4 modes. RAM intervention by integrating patient and family to help the patient’s cognators coping with recognizing and responding adaptive self-management to stimuli. Conclusions: The RAM guidelines were applicable for nurses to identify realistic and effective interventions for patients diagnosed with GBS involving the family in the hospital setting.